Certain aspects of using Z-score to assess cognitive disorders - V. V. Subbotin; I. N. Dushin; S. A. Kamnev; A. Yu. Аntipov (Вестник анестезиологии и реаниматологии)
Detailed psychological testing is needed to identify cognitive impairments after anesthesia and surgery. This problem can be solved by development of the program of combination psychological tests with their assessment based on the Z-score, also known as the standard deviation test.The objective: to determine reference values of psychological tests to assess the results of Z-score.Subjects and methods. The study was included 30 healthy volunteers and 43 patients who underwent surgery. The panel of psychological tests consisted of the clock drawing test, oral counting test, assessment of short-term memory, sequence set, Digit Symbol Substitution Test, and the classic Stroop test. The mean values and standard deviations were calculated for each of the groups to evaluate the test results by Z-score.Results. It was found that using standard deviations obtained in the group of healthy volunteers as reference values for Z-score resulted in a higher percentage of deterioration in the result of repeated tests compared to using reference values obtained in group of patients.Conclusion: When using Z-score for cognitive tests, it is better to use the means and SD obtained in a group of healthy volunteers taking into account the possibility of finding differences where there are none (type I error).